Effect of maleic hydrazide and waxing on ripening and quality of guava (Psidium guajava L.) fruit - Mohamed-Nour, Ibtissam A.; A. Abu-Goukh, Abu-Bakr (Gezira Journal of Agricultural Science; Vol 11 No 1 (2013), 2013)
The effect of postharvest treatment by maleic hydrazide (MH) and waxing on ripening and quality of white and pink guava fruits was evaluated at 20 + 1 O C and 85-90% relative humidity. MH at 250, 500 and 1000 ppm delayed fruit ripening by 2-6 days in both guava types compared to untreated fruits. The higher the concentration of MH, the more was the delay in fruit ripening. Waxing in addition to MH treatment resulted in 3-4 days more delay in fruit ripening, compared to MH treatment alone. The effect of MH treated and waxing in delaying fruit ripening was manifested in retarded climacteric peak of respiration, delayed peel colour development, reduced total soluble solids accumulation and decreased fruit softening.